El Perfil de Egreso del Ingeniero Agrónomo. Una Experiencia de Grupos de Discusión con Egresados - Córdova Duarte, Gabriel; Barbosa Jaramillo, Elva Rosa (Acta Universitaria, 2004)
This work presents a study of discussion groups in a panel with agronomist of the Universidad of Guanajuato to determine the bachelors degree graduate profile. The graduates suggested: to keep the practices in agricultural units, to improve the operating skills on agricultural and machinery equipment, to strengthen the basic agronomic area, to foment the management vision of commercialization, of products and of quality processes, formulate and evaluate productive projects, upbringing leaders and entrepreneurs; to develop creativity, punctuality, perseverance, discipline and humane relationship, to strengthen the humanist education and education by example; to create bonds between the school, the graduates, the universities, the teacher and the research with agricultural enterprises.
Keywords: Array; Array; Array; Array